Negosiasi Identitas Budaya Studi Fenomenologi Adaptasi Antarbudaya Mahasiswa Kalimantan di Semarang - Muhammad Faizul Hannan; Muhammad Nor; Urip Mulyadi (INDO PUBLISHING, 2026)
This study examines the cultural identity negotiation processes of students from Kalimantan who pursue higher education in Semarang, Central Java. Employing an interpretive phenomenological approach through in-depth interviews with 12 informants selected via purposive sampling, this research reveals the lived experiences of students confronting differences in values, norms, language, and customs between their home culture (Kalimantan) and the host culture (Javanese). The findings identify three phases of identity negotiation: (1) cultural shock and value disorientation upon initial arrival; (2) selective adaptation strategies through linguistic and social code-switching; and (3) the formation of a hybrid identity that integrates elements of both Kalimantan and Javanese culture. The study also finds the significant role of the Kalimantan diaspora community in Semarang as a safe space for maintaining home cultural ties while simultaneously serving as a bridge for adaptation to the local culture.